2019
DOI: 10.1530/rep-19-0028
|View full text |Cite
|
Sign up to set email alerts
|

Elevated heme impairs macrophage phagocytosis in endometriosis

Abstract: Endometriosis (EMS) is a chronic inflammatory disease characterized by the presence of extrauterine endometrial tissues. It has been previously reported that the refluxed blood containing viable endometrial tissues and the defective elimination of peritoneal macrophages in the pelvic cavity may involve in EMS pathogenesis. However, the mechanism by which macrophages exhibit attenuated phagocytic capability in EMS remains undetermined. Herein, we found that heme, the byproduct of lysed erythrocytes, accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Therefore, our measurements will test whether the tissue margins can be saved from dying by Mb knockout and/or iron chelation therapy. Third, prior studies found that high levels of heme/hemin caused impairment of phagocyte functions of chemotaxis and phagocytosis (11,(39)(40)(41)(42)(43). Given that pressure ulcers often have slough or eschar, we hypothesize that phagocytosis will also be impaired in mPI, and that sterile mPI will have slough, despite the absence of bacterial biofilm.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, our measurements will test whether the tissue margins can be saved from dying by Mb knockout and/or iron chelation therapy. Third, prior studies found that high levels of heme/hemin caused impairment of phagocyte functions of chemotaxis and phagocytosis (11,(39)(40)(41)(42)(43). Given that pressure ulcers often have slough or eschar, we hypothesize that phagocytosis will also be impaired in mPI, and that sterile mPI will have slough, despite the absence of bacterial biofilm.…”
Section: Introductionmentioning
confidence: 80%
“…Assorted immune cells, including NK cells, macrophages and T cells are reported to be dysregulated in patients with EMS. Impaired cytotoxicity of NK cells and reduced phagocytic capacity of macrophages permitted the ectopic endometrium to escape immune surveillance and clearance [10][11][12]27].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, immune disorder cannot shirk the responsibility in the progress of EMS [8,9]. Weakened phagocytosis ability of macrophages and reduced cytotoxicity of natural killer (NK) cells were found in peritoneal fluid of EMS, which were tightly linked with ectopic lesion formation [10][11][12]. Regulatory T cells (Tregs) have been extensively studied in the region of oncology for their important and irreplaceable role on immune tolerance [13,14].…”
Section: Ivyspringmentioning
confidence: 99%
“…Altogether, an inefficient clearance of shed menstrual fragments could prolong the survival of cells increasing the chance for implantation. Furthermore, the presence of uncleared debris and altered macrophage phenotype may further contribute to an inflammatory peritoneal environment promoting the establishment and persistence of endometriosis lesions (19)(20)(21).…”
Section: Dysregulation Of Inflammatory Mediatorsmentioning
confidence: 99%